Potensi Saccharomyces cerevisiae UNJCC y-87 dan asam amino terhadap kualitas casgot dan pertumbuhan kangkung (Ipomoea reptans) - Puspitasari, Anggraini Dwi; Surono , Surono; Sukmawati , Dalia (Buitenzorg: Journal of Tropical Science, 2024)
Water spinach (Ipomoea reptans) is a plant with quite high productivity every year. so that the growing media planted should be safe for the environment and plants. One planting medium that has many benefits for plants is casgot fertilizer which comes from the residue of black soldier fly (BSF) larvae that consume fermented feed with microorganisms, namely the yeast Saccharomyces cerevisiae UNJCC Y-87 and Amino Acids. This research aimed to determine the effect of the yeast S. cerevisiae UNJCC Y-87 and amino acids on the wet weight of BSF larvae and the effect of casgot fertilizer produced from BSF larvae residue on water spinach plants The method used was an experiment with an experimental design, namely a Completely Randomized Design consisting of 3 treatments with 5 repetitions of BSF fermented feed. Meanwhile, to apply casgot fertilizer to water spinach plants, 4 treatments were carried out with 4 repetitions. The results of the research showed that for fermented feed treatment with the addition of the yeast microorganism S. cerevisiae UNJCC Y-87 and amino acids of the wet weight of BSF larvae were superior in terms of morphology. Meanwhile, the results of the growth of water spinach plants showed that the treatment of casgot fertilizer containing the yeast S. cerevisiae UNJCC Y-87 was better in terms of plant morphology.   Keywords: amino acids, BSF, casgot, Ipomoea reptans, Saccharomyces cerevisiae